Student perceptions : Cell Phone Use at UW-EC. - Hartman, Kristin; Thelen, Andrea; Perry, Jason; Johnson, Jenna; Lillis, Nicole (My University, 2009)
This study investigated student perception of cell phone use on campus in academic and social settings.
Student Perception of Cell Phone Use in Social and Academic Settings.
Color poster describing research conducted by Kristin Hartman, Andrea Thelen, Jason Perry, Jenna Johnson, and Nicole Lillis, advised by Jennifer Becker.
Keywords: Cellular telephones--Use studies; Cellular telephones--Public opinion; College students--Attitudes; Posters